Sabab Al-Nuzul dan Asas Berlaku Surut dalam Hukum Pidana - Makinuddin Makinuddin (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2015)
Abstract: Al-Qurâ€™an is revealed by Allah as a guidance for mankind. Most of its verses were revealed without circumstantial events on which the verses were revealed. Meanwhile, there are also some of its verses which were revealed to answer or respond particular events or questions that can be easily understood from their historicity especially those which related to Islamic law. This particular events or questions are called sabab al-nuzul (context of revelation) in the study of QurÃ¡n. This research shows that there are many advantages of the context of the revelation associated with the legal verses. The wisdom and secret of the verses become the basis of the law promulgation to reach a public interest. As for the impact of the context of the revelation is that the derived law will be enforced since the legal event happened, and not since it was revealed. This rule is based on the principle of â€œthe derivation of Islamic constitution is understood from the particular context of the revelation and not based on the general meaning of the wordâ€, particularlyassociated with the criminal act which violatespublic or general interest. Thus, it is clear that the principle of legality is not always enforced in the Islamic criminal law. Under a certain condition, it may be applied retroactively if the criminal actdisturbs public interest. So that, this research will focus on the legal consequences of verses of al-Qurâ€™an which have the historical background and those which do not. Keywords: Reason of the revelation, certain historical background, retroactive, and muharabah Â Abstrak: Al-Qurâ€™an diturunkan ada yang tidak melalui sebab dan ini lebih banyak daripada yang melalui sebab dan ia merupakan wahyu yang menjadi petunjuk Allah bagiÂ umat manusia (hudan li al-nas). Sementara itu, ada juga yang melalui sabab al-nuzul, karena adanya fatrat min al-rasul (kekosongan umat manusia dari keberadaan Nabi dan Rasul) dan mengandung beberapa hikmah yang dalam, terutama terkait dengan pemahaman ayat-ayat hukum dalam al-Qurâ€™an. Melalui tulisan ini, ditemukan bahwa banyak manfaat sabab al-nuzul terkait dengan ayat hukum, di antaranya dapat diketahui hikmah dan rahasia diundangkannya suatu hukum dan perhatian sharaâ€™ terhadap kepentingan umum. Dampak sabab al-nuzul dengan penerapan asas berlaku surut (athar rajâ€™i), yaitu hukum yang diturunkan akan diberlakukan sejak peristiwa hukum (tindak pidana) itu terjadi, bukan sejak al-Qurâ€™an diturunkan, menurut kaidah sabab al-nuzul, al-â€˜ibrah bi khusus al-sabab, bukan al-â€˜ibrah bi â€˜umum al-lafz, terkait dengan tindak pidana yang mengganggu masyarakat atau kepentingan umum. Sehingga, menjadi jelas bahwa asas legalitas tidak selamanya diberlakukan dalam hukum pidana Islam maupun positif. Dalam kondisi tertentu dapat diberlakukan surut jika tindak pidana mengganggu kepentingan umum dan menguntungkan pelaku pidana jika terjadi perubahan peraturan dengan menganalogkan kepada peristiwa terdahulu melalui pendekatan sabab al-nuzul, bahkan dalam hukum pidana Islam lebih luas penerapan asas berlaku surut.